Narasi Hermeneutis Kajian Tafsir Jalalain di Pondok Pesantren Daarul Fatah Lampung - Lina Athifa Yusuf (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2021)
This paper departs from the phenomenon of living interpretation in the "Daarul Fatah" Islamic boarding school, Kampung Tegal Mukti, Lampung. At the Islamic boarding school there is a study of the Tafsir Jalalain book on a regular basis which is followed by students and the local community. This research was conducted in order to find out how the portrait of the implementation and how the reception of the community and students towards the study of Tafsir Jalalain at the Daarul Fatah Islamic Boarding School. Reception theory is used as an analytical knife to explore the response of the community and students to the study. The results of this study conclude that there are three important objectives conveyed by K.H. Dawud Yusuf, namely: first, Inviting students and the community to participate in the study. Second, to murajaah the Qur'an and provide an understanding of the Qur'an. Third, so that the community and students are broad-minded and knowledgeable. Meanwhile, the response of the community and students to the study was an increase in understanding of the Ahkam verses.